2014
DOI: 10.3390/s140712958
|View full text |Cite
|
Sign up to set email alerts
|

Short Chain N-Acyl Homoserine Lactone Production in Tropical Marine Vibrio sinaloensis Strain T47

Abstract: Quorum sensing (QS), acts as one of the gene regulatory systems that allow bacteria to regulate their physiological activities by sensing the population density with synchronization of the signaling molecules that they produce. Here, we report a marine isolate, namely strain T47, and its unique AHL profile. Strain T47 was identified using 16S rRNA sequence analysis confirming that it is a member of Vibrio closely clustered to Vibrio sinaloensis. The isolated V. sinaloensis strain T47 was confirmed to produce N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…As essential components of QS systems, AHLs have been detected in many Vibrio species, including V. sinaloensis, V. brasiliensis, V. ichthyoenteri, V. vulnificus, V. scophthalmi, V. anguillarum (Buchholtz et al, 2006 ; Garcia-Aljaro et al, 2008 ; Valiente et al, 2009 ; Li et al, 2010 ; Tan P. W. et al, 2014 ; Tan W. S. et al, 2014 ). However, to date, no systematic study of AHL distribution in V. alginolyticus are available, which hinders further understanding on the mechanisms underlying V. alginolyticus infection controls associated with QS system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As essential components of QS systems, AHLs have been detected in many Vibrio species, including V. sinaloensis, V. brasiliensis, V. ichthyoenteri, V. vulnificus, V. scophthalmi, V. anguillarum (Buchholtz et al, 2006 ; Garcia-Aljaro et al, 2008 ; Valiente et al, 2009 ; Li et al, 2010 ; Tan P. W. et al, 2014 ; Tan W. S. et al, 2014 ). However, to date, no systematic study of AHL distribution in V. alginolyticus are available, which hinders further understanding on the mechanisms underlying V. alginolyticus infection controls associated with QS system.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies reported a wide range of AHLs produced by Vibrio including C 4 -HSL, 3-OH-C 4 -HSL, C 6 -HSL, 3-oxo-C 6 -HSL, 3-OH-C 6 -HSL, C 8 -HSL, 3-OH-C 8 -HSL, C 10 -HSL, 3-OH-C 10 -HSL, 3-oxo-C 10 -HSL, 3-OH-C 12 -HSL, 3-oxo-C 12 -HSL (Buchholtz et al, 2006 ; Garcia-Aljaro et al, 2008 ; Valiente et al, 2009 ; Li et al, 2010 ; Purohit et al, 2013 ; Tan P. W. et al, 2014 ; Tan W. S. et al, 2014 ). In addition to these AHLs, we report for the first time C 12 -HSL and 3-oxo-C 14 -HSL for the genus Vibrio , suggesting a greater diversity of AHLs in the genus and this research area is worthy of further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Later, the same authors reported similar data for another marine bacteria belonging to the same genus Vibrio sp., V. sinaloensis strain T47. The isolated strain was confirmed to produce C4-HSL, and it also formed biofilms, which were inhibited by catechin [78].…”
Section: Quorum Sensing and Biofilm Developmentmentioning
confidence: 95%
“…Twenty four-h old cultures of the isolates were screened for their short-chain AHL production by cross-streaking them on NA plates with Chromobacterium violaceum CV026, a mini-Tn5 mutant which is incapable of producing its own autoinducer but is able to produce pigment when supplemented with external AHL. Violet pigmentation will be observed on C. violaceum CV026 if the isolates were able to produce short-chain AHL [32]. The type strain C. violaceum ATCC 12472 served as the positive control [33] and a local isolate Bacillus cereus CRK1-1 served as the negative control [34].…”
Section: Detection Of Short-chain Ahl Productionmentioning
confidence: 99%